(untitled) (Journal of Dhaka Medical College, 2023)
Back ground: The Visceral Adiposity Index (VAI) is an empirical mathematical model, genderspecific, based on simple anthropometric (BMI and WC) and functional parameters (triglycerides (TG) and HDL cholesterol (HDL)), and indicative of fat distribution and function. Methods: This is a Cross sectional study. It was carried out in the department of Biochemistry, BSMMU from July 2015- June 2017. Type 2 Diabetes Mellitus patients attending in outpatient Department of Endocrinology and Metabolism, BSMMU were our study population. The cutoff value for VAI was considered as 3. Results: We enrolled 105 participants in this study. Among them 41 were male and 64 were female. There was significant difference between male and female in terms of height, weight and BMI. Male had greater height (p =0.01) and weight (p =0.01) than female. Female had greater BMI (p =0.01) than male. The majority of male and female scored above the cut off value of VAI which were 63.4% and 59.4% respectively. The mean value of biochemical parameters TG, FBG and HbA1c were significantly different on the basis of cutoff point of VAI (d”3 and > 3). There is increased TG, FBG and HbA1c and decreased HDL-C with the cut off value more than 3 in VAI. We found significant strong positive correlation with HbA1c with FRS (r= +.631, p=<0.001) and VAI (r= +.596, p=<0.001) Conclusion: High Visceral Adiposity Index is associated with Type 2 diabetes mellitus and increased cardiovascular risk J Dhaka Med Coll. 2021; 29(1): 68-75